Collective brand reputation - Volker Nocke; Roland Strausz (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2022)
We develop a theory of collective brand reputation for markets in which product quality is jointly determined by local and global players. In a repeated game of imperfect public monitoring, we model collective branding as an aggregation of quality signals generated in different markets. Such aggregation yields a beneficial informativeness effect for incentivizing the global player. It however also induces harmful free-riding by local, market-specific players. The resulting tradeoff yields a theory of optimal brand size and revenue sharing that applies to platform markets, franchising, licensing, umbrella branding, and firms with team production.
Keywords: 330; Collective branding; reputation; free-riding; repeated games; imperfect monitoring